Socio-Religious Transformation and Resilience of Islamic Identity in Kauman Village of Yogyakarta - Arifin, Muhammad; Alya, Nabila Ulamy (Pascasarjana IAIN Pontianak, 2024)
This article aims to study and describe the changes occurring in Kauman Village. The targeted transformation involves converting Kampung Islam into a tourist village. This study aims to examine how Kauman’s sacred religious space changed into a profane tourist area, from Kampung Islam (Islamic Village) to Kampung Pariwisata (Tourist Village). This research aims to explore how the religious and sacred Kauman neighborhood transformed into a profane tourist space. This study employed qualitative methods that involved observation, in-depth interviews, and a review of relevant literature to collect data. The research findings are presented as an account of direct observations of ongoing religious events and interview findings from respondents. This research shows that Muhammadiyah’s entry as a modern movement in religious affairs represents a socio-religious transformation in response to unstoppable global flows of information and globalization. Despite various challenges to their values this study found that Islamic values have grown stronger and continue to exist. The Kauman community shows strong determination and actively works to maintain its identity. While adapting Islamic identity materials to represent Islam and Muhammadiyah, the community ensures that fundamental religious values remain intact.